Pelatihan English as a Second Language Instruction in the Classroom - Setianingsih, Tri; Nafisah, Bq Zuhrotun; Imansyah, Imansyah; Utama, I Made Permadi; Qomariyah, Siti Syafi’atul (LPPM Universitas Bumigora, 2024)
The importance of English as an international language makes the head of SMAIT Tunas Cendekia wants to make this school as a bilingual. To realize this goal, one way is to improve teachers this school to get English language training. This is what makes our team from the UNDIKMA English Language Education Program provides intensive English language training at the school to improve the teachers’ English skill. The method used for this service was sharing, theory and practice. The result from process evaluation: training preparation: 80% well and 20% sufficient, Implementation: 75% good, 25% sufficient, Aspects of Presenter competency: 90% good, 10% sufficient, Training materials; 80% good, 20% sufficient. Evaluation of result: first day, 95% of the material was absorbed well and 85% could be implemented well, second day, 85% of the language instruction material could be memorized well, and 80% could be put into practice, third day of the training material providing instructions in English in class, 90% could be absorbed well, and 85% could be put into practice directly, fourth day of implementation, giving instructions in English in class could be well absorbed 90% and 85% could be put into practice by the teachers.